Pharmacoepidemiological aspects of antibacterial therapy of salpingoophoritis in hospital settings - E. A. Ushkalova; L. Yu. Chernikova; I. D. Evtushenko; E. V. Karakulova; V. A. Fokin; M. V. Belousov (Бюллетень сибирской медицины)
The purpose of the study is an analysis of the consumption of antibacterial drugs in the therapy of salpingoophoritis in hospital settings and evaluation of changes in the real clinical practice of antibiotic therapy after the introduction of the “Order of medical care for the profile “obstetrics and gynecology...”.Materials and methods. In a retrospective study, an assessment was made of the prescriptions of antibacterial drugs in the therapy of salpingoophritis in specialized treatment and prophylactic institutions of the city of Tomsk in the period 2010–2014. The analysis included 160 case histories. The structure of prescriptions was evaluated on the basis of the application of anatomical-therapeutic-chemical classification and international non-proprietary names (INN), the structural improvement factor K. Gatev was calculated. To quantify the consumption of medications, the calculated daily dose (PDD) was used.Results. Comparative analysis of antibacterial therapy of salpingoophoritis in hospital before and after the introduction of the “Order of medical care for the profile of «obstetrics and gynecology...”. Leading groups of antibacterial drugs were identified.   А comparative analysis of the frequency of assignment of various INN was made. The К. Gate’s coefficient was 0.281. The calculation of the average prescribed daily doses of antibacterial drugs was performed.Conclusion. The review of the consumption of antibacterial drugs for salpingoophoritis therapy in hospital settings before and after the introduction of the “Order of medical care for the profile “obstetrics and gynecology...”, showed that the range of antibacterial drugs used increased from 18 to 24 INN, mainly due to the inclusion of modern medicines. In the structure of appointments in 2013–2014, the proportion of drugs not recommended for use by the «Order of medical care for the profile of «obstetrics and gynecology» was 37.5%. It was found that PDD clarithromycin, clindamycin and cefotaxime did not meet the recommended dosing regimens specified in the clinical recommendations for antibiotic therapy. The gap between actual clinical practice and existing clinical recommendations determines the need for in-depth pharmacoepidemiological evaluation to identify the causes and develop measures of an organizational and educational nature to optimize the use of medications.